(3Md GdTchc ef cJGH CbdjOSs - (3GHf GdgjKe , eMeO Hf GdMSf Hf GdgjKe, CHh Ydj HWdjehS GdKGfj,J (B430 (3g` s
(3ChdgG (B:s
(3cd eYfi HaQV MbjbJI hjNV HGdHOjgI NhGUg hJTGHg ai HYV CMhGdg hbO Cda ai Md Tchc gPG GdcJGH s
(3BNQgG (B:s
(3GdTcd GdQGHY YTQ EPG cGfJ GYOGOce cGfJ hGYOGO CNj Ydi YOJgG cd YOOjf ef GdChd Ydi fSHI YOOjf ef GdGNQ aEfgG ai fSHI GdeSGhGI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B83 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B225s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3Gdadcs